2015
DOI: 10.3390/ijms16047707
|View full text |Cite
|
Sign up to set email alerts
|

Combined Enzymatic and Mechanical Cell Disruption and Lipid Extraction of Green Alga Neochloris oleoabundans

Abstract: Microalgal biodiesel is one of the most promising renewable fuels. The wet technique for lipids extraction has advantages over the dry method, such as energy-saving and shorter procedure. The cell disruption is a key factor in wet oil extraction to facilitate the intracellular oil release. Ultrasonication, high-pressure homogenization, enzymatic hydrolysis and the combination of enzymatic hydrolysis with high-pressure homogenization and ultrasonication were employed in this study to disrupt the cells of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 36 publications
5
44
0
1
Order By: Relevance
“…[29] This result was confirmed by similar results from other studies. [30,31] Determination of the sugar content of the lipidextraction by-products…”
Section: Comparison Of the Fatty Acid Compositionmentioning
confidence: 99%
“…[29] This result was confirmed by similar results from other studies. [30,31] Determination of the sugar content of the lipidextraction by-products…”
Section: Comparison Of the Fatty Acid Compositionmentioning
confidence: 99%
“…The results revealed that A. brasilense boosted the growth of C. vulgaris through indole acetic acid (IAA) utilization of the amino acid tryptophan conversion process [38]. The Chlorella vulgaris exhibits poor harvesting due to flocculation efficiency of 0%-2% [39], but its co-culturing with bioflocculant-producing bacteria improved the harvesting. This highlights cost-effective production of microalgal biomass for biofuels.…”
Section: Co-culture Methodsmentioning
confidence: 99%
“…For instance, Passos and Ferrer (2015) demonstrated a break in the outer structure of the cell wall and damages in the intracellular structure after thermal pretreatment of Oocystis sp. while Wang et al (2015) showed a break down in the cell wall and leakage of intracellular material of Neochloris oleoabundans after combined mechanicalenzymatic pretreatment.…”
Section: Cell Morphology Observation Before and After Biocatalysts Prmentioning
confidence: 98%